Effectiveness of Combined Shallot Skin Compost and NPK Fertilizer on Cayenne Pepper (Capsicum frutescens) Plants in Ultisol Soil - Simbolon, Teddy Aryanto; Mutryarny, Enny; Purnama, Indra (Department of Chemical Engineering, Faculty of Engineering, UNRI, 2025)
The cultivation of cayenne pepper (Capsicum frutescens L.) is important due to its widespread use in the food and pharmaceutical industries, as well as in everyday cooking. This study aimed to evaluate the effectiveness of combining shallot skin compost and NPK fertilizer on the growth and yield of cayenne pepper plants grown in Ultisol soil. The experiment was conducted using a Completely Randomized Design (CRD) in a factorial arrangement, with two factors: shallot skin compost (0, 200, 400 g per polybag) and NPK fertilizer (0, 13, 25 g per polybag), each replicated three times. The observed parameters included plant height, stem diameter, number of branches, fruit count, and fruit weight. Data were analyzed using ANOVA followed by Duncan's Multiple Range Test (DMRT) at a 5% significance level. Results indicated that the application of 200 g of shallot skin compost and 25 g of NPK fertilizer per polybag significantly improved plant height, stem diameter, and overall fruit production. Furthermore, a significant interaction between shallot skin compost and NPK fertilizer was observed, particularly in terms of fruit yield and weight. This study suggests that combining organic and inorganic fertilizers can enhance the productivity of cayenne pepper plants in Ultisol soil, offering a sustainable approach to increasing crop yield. Further research is recommended to explore the long-term effects of these treatments on soil health and plant growth.